2013
DOI: 10.1111/1541-4337.12021
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Components of Amaranth Seeds and Vegetables: A Review on Composition, Properties, and Uses

Abstract: A few decades ago Amaranthus was rediscovered as a most promising plant genus that may provide high-quality protein, unsaturated oil, and various other valuable constituents. Since then research has focused on various Amaranthus spp. and has been rapidly expanding, and a large number of reports have been published. Several review articles focusing on different aspects, such as botanical, agrotechnological, compositional, biological, chemical, and technological properties, as well as applications and health eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
274
2
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(307 citation statements)
references
References 201 publications
(373 reference statements)
16
274
2
15
Order By: Relevance
“…The results confirm what is documented in the literature that Amaranth leaves and grains are nutritionally superior to cereal grains (Venskutonis & Kraujalis, 2013;Escudero et al, 1999;Makobo et al, 2010). …”
Section: Effect Of Adding Amaranth Leaf Powder On Mineral Compositionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results confirm what is documented in the literature that Amaranth leaves and grains are nutritionally superior to cereal grains (Venskutonis & Kraujalis, 2013;Escudero et al, 1999;Makobo et al, 2010). …”
Section: Effect Of Adding Amaranth Leaf Powder On Mineral Compositionsupporting
confidence: 91%
“…As a rich source of nutrients (including protein and essential amino acids) (Venskutonis & Kraujalis, 2013;Alegbejo, 2013), Amaranth leaf powder would improve the nutrient content of food it is added to, such as snacks (Chavez-Jauregui et al, 2003).…”
Section: Effect Of Adding Amaranth Leaf Powder On Protein Content Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It cleanses the blood and is used to treat kidney disease and jaundice. It possesses antioxidant, anti-atherosclerotic, anti-helminthic, antimicrobial, anti-cancer, anti-inflammatory, anti-diabetic and antipyretic properties which are due to its high polyphenolic contents (Ashok Kumar et al 2011;Girija et al 2011;Venskutonis and Kraujalis 2013;Miraj 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lupine seeds have an ameliorating effect on glucose tolerance test in the fish Clarias gariepinus (Al-Salahy and Mahmoud, 2004). It had been suggested that lupine seeds might have higher antioxidant activity and contains a high amount of arginine, aspartate and glycine (Oomah et al, 2006), tocopherols (Venskutonis and Kraujalis, 2013).…”
Section: Discussionmentioning
confidence: 99%